Indeks Kepuasan Masyarakat (IKM) Kelompok Nelayan Tuna Terhadap Program CSR PT Pertamina RU II Dumai - Hildawati Hildawati (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2020)
CSR is a commitment of business people to continue to act ethically, operate legally and contribute to economic growth, along with improving the quality of life of employees and their families as well as improving the quality of local communities and communities in the business environment within the company's business environment. PT Pertamina RU II Dumai is one company that continuously carries out CSR activities with various target groups in the community. One of the beneficiaries of PT Pertamina RU II Dumai's CSR program is the Tuna Fishermen Group with the Fishermen Community Empowerment Program (Minapolitan Village Development Pilot Project). This study is to measure community satisfaction with the CSR program that has been carried out so that concrete steps can be found to increase the benefits of program implementation. The population of this research is the Tuna Fishermen Group with 11 members. The sampling technique is the Census. The data method used a questionnaire and observation. Data analysis refers to Permen PAN and RB No. 14 of 2017. From the analysis conducted, it was obtained that the IKM value was 3.25 with the IKM value converted to 81.25 which could be interpreted as “Good” for the Performance Quality Program.